Case Study of Implementation of Administrative Innovation in Improving the Quality of Health Services - Nelwetis; Antik Pujihastuti (Miracle Journal Get Press, 2024)
Administrative innovation is crucial for enhancing health service quality. As health systems evolve, effective administration can expedite service delivery, minimize patient wait times, and enhance the accuracy of patient data. In today's society, there are heightened expectations for health service quality, including information accuracy and accessibility. Implementing innovative, technology-driven administrative systems can bolster public trust in healthcare institutions.This study investigates the changes before and after the implementation of such innovations, assessing their effectiveness in addressing common administrative challenges. Employing a qualitative case study methodology with a descriptive approach allows for an in-depth exploration of administrative innovation processes in specific health facilities and their impacts on service quality. Key respondents include health workers—doctors, nurses, and administrative staff—directly involved in these innovations, alongside patients who evaluate their satisfaction with the changes.Findings indicate positive responses from both health workers and patients regarding the innovations. Health workers reported increased efficiency in their tasks, while patients experienced improved service quality. Despite challenges such as the need for training and concerns over data privacy, there is optimism for continued development of these innovations to foster a more modern and efficient healthcare system. Ultimately, an integrated approach to administrative innovation aims to achieve safer, more efficient, and higher-quality health services accessible to all community members.